Effect of Season and Increased Temperature on Survival, Roe Enhancement, and Reproductive Cycle of the Green Sea Urchin (Strongylocentrotus droebachiensis) Collected from Four Relatively Close Sites in Northern Norway. (17th April 2023) - James, Philip; Evensen, Tor; Johansson, Gunhild
Abstract : A series of three trials were conducted in the North of Norway at different times of the year. The trials consisted of harvesting sea urchins from four sites, situated within 5 km of each other and then holding them in land-based enhancement facilities. They were held at ambient seawater temperatures as well as ambient plus 3.0°C. Samples were taken from the wild at the time of collection and at the end of the enhancement period as well as from the enhanced sea urchins from each site. Results showed that utilising the sea urchins from a variety of sites, even from areas where there is an abundance of sea urchins (sea urchin barrens) and the Gonad Index (GI) is almost always low, is viable in terms of the final, post roe enhancement GI. The results of the study indicate that differences in initial and final GI and the increase in GI between the sites, despite the relatively close proximity, show site selection is most likely not as important as ease of harvesting and sea urchin availability and the positive environmental impact from removal of sea urchins and these are the factors that harvesting strategies should focus on. The study has shown that it is possible to have a relatively consistent roe enhancement from S. droebachiensis from the North of Norway regardless of seasonality (time of year), site selection, and initial GI. Relatively small changes (up to 3°C) in the seawater temperature appear to have a slightly negative impact on enhancement efforts. However, this may vary when larger differences in temperature are experienced.